Socio-environmental governance in brazilian northeast coastal capitals - Medina Velasco, Miriam; Lima dos Santos, Hugo Vigas; Vieira Dantas, Clélia Maria (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper analyzes how eight Brazilian Northeast’s coastal capitals has structured themselves to deal with socio-environmental issues, aiming to comprehend the transformations they faced and identify their progress and limitations. Simultaneously, it also tries to map the levels of articulation with society and/or strengthening of socio-environmental governance during the first two decades of the twentieth-first century. To examine this issue, we worked with official data available at government agencies’ websites. This allowed us to build our analysis on a systemic, multi-referential, historical, institutionalist and pluralistic perspective on the environmental management mechanisms applied by the studied cities. The results reveal their diversification of management offices, mechanisms and processes. The proposed approach also contributes to the reflection on the challenges faced by the articulation between government and society in search of living conditions enhancement, indicating the concerns as to its incipient stage regarding the mobilization towards 2030 Agenda and emphasizing the potentialities of governance models in a country signatory to the Global Compact.